Overwintering temperature affects lipid and fatty acid metabolism in hepatopancreas and ovary of female mud crab Scylla paramamosain - Kaijia Yu; Hanying Xu; Ce Shi; Chunlin Wang; Changkao Mu; Yangfang Ye; Shujian Chen; Ronghua Li; Qingyang Wu (Aquaculture Reports)
The influence of four overwintering temperatures, namely 8 ℃, 12 ℃, 16 ℃, and 20 ℃, on lipid metabolism and fatty acid profile in the hepatopancreas and ovary tissues of female mud crab Scylla paramamosain was investigated during eight weeks. According to the results, the hepatosomatic index (HSI) of the crabs after overwintering at 16 ℃ and 20 ℃ was significantly lower than that pre-overwintering (P < 0.05), however, overwintering did not affect the gonadosomatic index (GSI) (P > 0.05). Moreover, the increased overwintering temperature significantly decreased the triglyceride (TG) content in the hepatopancreas (P < 0.05), while the ovary tissue remained unaffected (P > 0.05). Hemolymph biochemical indices demonstrated that the level of low-density lipoprotein cholesterol (LDL-C) increased markedly as temperature rose (P < 0.05). In addition, the fatty acid profile of hepatopancreas tissue did not change significantly at different overwintering temperatures (P > 0.05), however, the content of EPA in ovary tissue significantly increased with the temperature rise (P < 0.05). Furthermore, the rise in temperature significantly upregulated the expressions of lipid catabolism genes (hsl, cpt Ⅰ) and lipid transport genes (fabp3, fatp4), while significantly downregulated the expressions of lipid synthesis genes (acc, g6pd) in the hepatopancreas. Meanwhile, the temperature did not affect the expressions of lipid synthesis genes (acc, fas, g6pd) and lipid catabolism genes (hsl, aco, cpt Ⅰ, cpt Ⅱ) in ovary tissue. Still, the temperature increase significantly upregulated the expressions of PUFA synthesis genes (Δ6fad, elovl4). In conclusion, overwintering at 16 ℃ and 20 ℃ promoted the process of lipid catabolism and transport in hepatopancreas tissue of mud crabs. However, overwintering at 20 ℃ was beneficial for accumulating more EPA in ovary tissue from a breeding perspective.